Motif Mahasiswa Pengguna Aplikasi Tiktok (Analisis Teori Uses and Gratification Pada Mahasiswa Universitas Negeri Padang) - Rilma, Nuresti Ayu; Agnesia, Rara (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
Social media has become a part of people's lives and cannot be separated from daily activities such as Facebook, Instagram, YouTube, and TikTok. Social media is not only used as a means of conveying information, but also as a means of establishing communication. The use of social media for society cannot be separated from the motive or reason of someone in using it. Like the TikTok application that is almost liked by all circles. The theory of Uses and Gratification is a theory that explains the reasons someone uses social media and what are the functions of the media. This study aims to discuss or analyze the motives of students in using the Tiktok application. The respondents came from students of Padang State University. The data collection method was carried out by sharing questionnaire links and interviews. Based on observations made, it was found that there were several motives for using the Tiktok application for UNP students. The results of observations show that Tiktok is used as a medium of entertainment, meeting needs in terms of information and education. In addition, Tiktok is also used as a place to vent emotions or find motivation for users' lives.